1984
DOI: 10.1002/pol.1984.170220624
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight phenomena at high conversions in the Ziegler–Natta polymerization of butadiene

Abstract: A Comparison between two different feedstocks in the homogeneous polymerization of butadiene has been conducted. The conversion and molecular weight trends were essentially the same for both feedstock systems. Changes in polydispersity at high conversions could not be explained by a living polymerization mechanism. A reaction scheme involving reuse of active cobalt centres combined with termination has been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Additionally, we have studied the effect of catalyst concentration, water:alkylaluminum ratio (W/Al), and chain transfer agent on polymerization of BD in cyclohexane and toluene. The selected studies in toluene reported by Honig et al are shown to be in agreement with our values. , Noticeably, important variables like water:alkylaluminum ratio, molecular weight, polydispersity index (PDI), and rate constants are studied as valuable information for butadiene polymerization.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, we have studied the effect of catalyst concentration, water:alkylaluminum ratio (W/Al), and chain transfer agent on polymerization of BD in cyclohexane and toluene. The selected studies in toluene reported by Honig et al are shown to be in agreement with our values. , Noticeably, important variables like water:alkylaluminum ratio, molecular weight, polydispersity index (PDI), and rate constants are studied as valuable information for butadiene polymerization.…”
Section: Introductionsupporting
confidence: 90%
“…11 It can be seen that the polymerization rate follows the order cyclohexane > toluene > EB, in reverse order with their π-electron density. Reaction is considered to be pseudo-first-order in toluene according to Honig et al 28,29 This also signifies that the parameter related to π-donation ability of the solvent is the determinant factor for controlling the reaction progress.…”
Section: Kinetic Behavior In Differentmentioning
confidence: 99%
See 1 more Smart Citation